2014
DOI: 10.1155/2014/742032
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genotypic Characterization of AtypicalListeria monocytogenesandListeria innocuaIsolated from Swine Slaughterhouses and Meat Markets

Abstract: In the last decade, atypical Listeria monocytogenes and L. innocua strains have been detected in food and the environment. Because of mutations in the major virulence genes, these strains have different virulence intensities in eukaryotic cells. In this study, we performed phenotypic and genotypic characterization of atypical L. monocytogenes and L. innocua isolates obtained from swine slaughterhouses and meat markets. Forty strains were studied, including isolates of L. monocytogenes and L. innocua with low-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 21 publications
2
8
1
Order By: Relevance
“…Specific primers were designed as selective target of virulence genes in listeria monocytogenes such as Iap gene to delineate the different species of listeria spp as reported by Klein and Juneja (1997). Iap gene was detected in all Listeria strains (100%) and these results were similar to those obtained by Gelbicova and Karpiskova (2012) in the Czech Republic, Jamali et al, (2015) in Iran, Moreno et al (2014) in Brazil, and Wang et al, (2015) in China. Moreover, (Bhunia, 2008;Furrer et al, 1991, andSwaminathan et al, 2007) have been reported that the presence of multiple virulence factors in L. monocytogenes strains such as Iap gene may be act as a potential cause of human listeriosis due to improved entry into cells, escape from the vacuole and intracellular spreading.…”
Section: Species-specific Primers Targeted Against Virulence Genes Ofsupporting
confidence: 77%
“…Specific primers were designed as selective target of virulence genes in listeria monocytogenes such as Iap gene to delineate the different species of listeria spp as reported by Klein and Juneja (1997). Iap gene was detected in all Listeria strains (100%) and these results were similar to those obtained by Gelbicova and Karpiskova (2012) in the Czech Republic, Jamali et al, (2015) in Iran, Moreno et al (2014) in Brazil, and Wang et al, (2015) in China. Moreover, (Bhunia, 2008;Furrer et al, 1991, andSwaminathan et al, 2007) have been reported that the presence of multiple virulence factors in L. monocytogenes strains such as Iap gene may be act as a potential cause of human listeriosis due to improved entry into cells, escape from the vacuole and intracellular spreading.…”
Section: Species-specific Primers Targeted Against Virulence Genes Ofsupporting
confidence: 77%
“…For example, hemolytic L. innocua strains (as discussed above) could be considered atypical Listeria . Similarly, a number of atypical (including non-hemolytic) L. monocytogenes have been described (Burall et al 2014 ; Hof 1984 ; Moreno et al 2014 ; Pine et al 1987 ). While one could argue that these non-hemolytic L. monocytogenes strains that were described before the taxonomic description of L. marthii may indeed have been L. marthii , a number of these strains were confirmed to truly be atypical L. monocytogenes .…”
Section: Phenotypic Characteristicsmentioning
confidence: 96%
“…Interestingly, this same hemolytic L. innocua isolate (FSL J1-023) did not contain the complete inlAB operon, which encodes two internalins (InlA and InlB) that are critical virulence factors, but only contained inlA . Other atypical L. innocua strains encoding LiPI-1 and inlA have been found in Brazil (Moreno et al 2014 ) and in Korean-imported clams (Johnson et al 2004 ), suggesting that these atypical L. innocua strains are widespread. The specific implications that the presence of inlA and the absence of inlB have on virulence in humans and other animals remain to be determined.…”
Section: Virulencementioning
confidence: 99%
“…The fragment of studied Inlc gene was characterised from different Listerial pathogens and demonstrated the presence of conserved regions at the 5'/3' ends and a species-specific internal region. This gene was used to design primers that specifically amplify Listeria spp., (Moreno et al, 2014) and that it could be used for specific identification using the DGGE/ CDGE method. Two primers were identified for the region of the sequences that were conserved among different Listeria spp.…”
Section: Discussionmentioning
confidence: 99%